Synthesis of Polyanionic C5-Modified 2′-Deoxyuridine and 2′-Deoxycytidine-5′-Triphosphates and Their Properties as Substrates for DNA Polymerases - Dutson, Claire (Molecules, 2021)
Modified 2′-deoxyribonucleotide triphosphates (dNTPs) have widespread applications in both existing and emerging biomolecular technologies. For such applications it is an essential requirement that the modified dNTPs be substrates for DNA polymerases. To date very few examples of C5-modified dNTPs bearing negatively charged functionality have been described, despite the fact that such nucleotides might potentially be valuable in diagnostic applications using Si-nanowire-based detection systems. Herein we have synthesised C5-modified dUTP and dCTP nucleotides each of which are labelled with an dianionic reporter group. The reporter group is tethered to the nucleobase via a polyethylene glycol (PEG)-based linkers of varying length. The substrate properties of these modified dNTPs with a variety of DNA polymerases have been investigated to study the effects of varying the length and mode of attachment of the PEG linker to the nucleobase. In general, nucleotides containing the PEG linker tethered to the nucleobase via an amide rather than an ether linkage proved to be the best substrates, whilst nucleotides containing PEG linkers from PEG(6) to PEG(24) could all be incorporated by one or more DNA polymerase. The polymerases most able to incorporate these modified nucleotides included Klentaq, Vent(exo-) and therminator, with incorporation by Klenow(exo-) generally being very poor.